The nexus of a human rights-based approach and microfinance. Issue 2 (17th February 2020) - Noh, Jae-Eun
ABSTRACT: This article explores the interaction between a human rights-based approach (HRBA) and pre-existing dominant development practices – microfinance in the context of Bangladesh. A case study of an NGO shows that its HRBA and microfinance challenged and influenced each other. The dialogue between the HRBA and microfinance was promoted by locally based practitioners who know both discourses and local contexts. The findings suggest that hybrid practices of a HRBA and microfinance were developed as a strategic choice to respond to local needs. Noted tensions between a purist approach and a strategic approach warrant further investigation.